Implementasi Pertanian Organik Pada Proses Budidaya Dan Penanganan Pascapanen Bunga Marigold Di UPT Pelatihan Pertanian Singosari - Oktavyan Dwi Irianto; Noor Rizkiyah; Muhammad Azriel Yahya; Nadhif Syathiril Anwar; Elvin Syah Huzaimi (Lembaga Pengembangan Kinerja Dosen, 2024)
The implementation of organic farming on marigold flowers at the Singosari Agricultural Training UPT starts from the initial phase of cultivating marigold flowers using organic products, namely Rice Mol, Banana Weevil Mol, PGPR, POC and others. The aim of this research is to determine the implementation of organic farming on marigold flowers at the Singosari Agricultural Training UPT and to determine the process of processing products from marigold flowers at the Singosari Agricultural Training UPT. The method used in this research is observation and interviews with related parties. The results of this research are the implementation of organic farming on Marigold flowers at the Singosari Agricultural Training UPT starting from the initial phase of Marigold flower cultivation using organic products, namely Rice Mol, Banana Weevil Mol, PGPR, POC and others. The processing of marigold flowers that has been carried out is that the flowers that have been harvested are processed in the form of washing, separating the flower heads, drying and packaging.